Analysis of Financial Literacy and Digital Literacy on the Sustainability of Micro, Small and Medium Enterprises (MSMEs) - Putra, Agus Tri; Inanna; Tahir, Thamrin; Mustari; Hasan, Muhammad (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to find out or analyze how financial literacy and digital literacy are implemented in business continuity in MSMES in the Taman Kalong tourist area, Soppeng Regency. The research method used in this research is a qualitative descriptive method. Data was collected through three main techniques, namely observation, interviews and document collection, involving main informants and additional informants. The collected data is then analyzed through the stages of data reduction, data presentation, and drawing conclusions. The results of this research show that the application of financial literacy and digital literacy has a significant role in supporting business continuity. Business sustainability is the most important factor that must be achieved by business actors. Growth, profits and humanitarian contributions are the main results that must be achieved by business actors. This achievement is of course supported by several factors, namely business actors' understanding of finance and understanding of digital which is a supporting factor for business continuity. This is also very consistent with the results of research conducted on small, micro and medium businesses in the Taman Kalong Tourism Area, Soppeng Regency